Growth of three color hybrids of sweet paprika under greenhouse conditions (2015)
The color varieties of sweet paprika are conquering the Colombian vegetables markets, not only because of their fancy colors, but also because they are one of the best sources of ascorbic acid and carotenoids as well as phenolic compounds, important in the human diet. Therefore, basic studies related to the growth and development of the available imported varieties under greenhouse conditions on the Bogota Plateau are required. In a completely randomized block design with five replicates, biometric parameters of the hybrids Plinio, Menta RZ and Orangery were evaluated, showing that the latter one was statistically different for leaf area, leaf area index and number of leaves during the 20 study weeks, while the dry matter in the leaves, stems and roots showed no differences between the varieties. Although, 'Orangery' exhibited the highest percent of final allocation of accumulated dry matter in the fruits, being, in general, the most promising hybrid for cultivation under the research conditions.